Epidemiology of diffuse large B-cell lymphoma (DLBCL) and follicular lymphoma (FL) in the United States and Western Europe: population-level projections for 2020–2025. Issue 1 (2nd January 2022) - Kanas, Gena; Ge, Wenzhen; Quek, Ruben G. W.; Keeven, Katie; Nersesyan, Knar; , Jon E. Arnason
Abstract: Diffuse large B-cell lymphoma (DLBCL) and follicular lymphoma (FL) treatments have been rapidly evolving for patients treated in later lines of therapy (LoT). Country-specific cancer registry data for the US and Western Europe (WE) were combined with physician survey results to project the incidence, prevalence, and number of DLBCL and FL patients eligible for and treated by LoT between 2020 and 2025. The total number of incidents and prevalent cases of DLBCL and FL is expected to increase between 2020 and 2025 in the US and WE. 56% and 53% of the third line plus (3L+) eligible DLBCL patients and 60% and 55% of eligible FL patients initiated treatment in the US and WE, respectively. Further research is warranted to understand the reasons behind the high proportion of treatment eligible patients who do not initiate treatment, and potential differences between countries, especially in the 3L + settings.